2020
DOI: 10.3233/npm-190205
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of the mothers of infants hospitalized in the neonatal intensive care unit (NICU)

Abstract: BACKGROUND: The mother-newborn relationship is more important in neonates hospitalized in the NICU than in healthy neonates. This study was conducted to explore the experiences of the mothers of infants hospitalized in the NICU. MATERIALS AND METHODS: This qualitative study was done in 2016 by adopting a conventional content analysis approach. Thirty-five mothers in the NICUs, Imam Hossein Hospital and Fatemieh Hospital were selected. Their experiences were assessed using in-depth individual semi-structured in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 20 publications
0
10
0
4
Order By: Relevance
“…Quality togetherness of mother and baby is important for a healthy mother-infant attachment [11]. It has been stated in previous studies that babies develop mentally and physically faster as mothers have more opportunities to be with and care for their babies [20,22,26].…”
Section: Maternal-health Provider's Interaction and Expectationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Quality togetherness of mother and baby is important for a healthy mother-infant attachment [11]. It has been stated in previous studies that babies develop mentally and physically faster as mothers have more opportunities to be with and care for their babies [20,22,26].…”
Section: Maternal-health Provider's Interaction and Expectationsmentioning
confidence: 99%
“…Similarly, previous studies reported that mothers were unable to deal with doctors at all, and they complained that communicating with health staff was very difficult and they used negative communication methods, which pushed a mother to loneliness. Although communication skills differ from person to person, it is thought that the communication of healthcare professionals with mothers, even at a basic level, will ensure the adaptation of mothers to NICU and reduce the workload of these professionals [5,11,23,24,29,30].…”
Section: Maternal-health Provider's Interaction and Expectationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it encompasses preparation of neonates for successful discharge and parents for their roles in neonatal care (Lake et al, 2016). NICU nurses play a significant part in assessing risk factors for physiological and psychological conditions in neonates, promoting their growth and developmental process, encouraging parent attachment, and providing family-centered care, all of which are associated with quality of care (Nazari et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Mothers with an infant in the NICU can feel a loss of control and disconnect from their infant. These factors can present challenges that affect the parenting role such as delayed maternal attachment and reduced capacity for emotional bonding [7]. Parents experience considerable stress, distress, and di culty maintaining their caregiver role [8].…”
Section: Introductionmentioning
confidence: 99%